Method of forming profiles of arbitrary electron beams; RREPS-15. Radiation from Relativistic Electrons in Periodic Structures - Cherepennikov Yu. M. Yuriy Mihaylovich; Stuchebrov S. G. Sergey Gennadevich; Danilova I. Irina; Miloichikova I. A. Irina Alekseevna (Poster Session, 2015)
Title screen.